Prevalence and Associated Factors of Loneliness Among National Samples of In-School Adolescents in Four Caribbean Countries - Supa Pengpid (2022)
Background: The goal of the study was to estimate the prevalence and correlates of loneliness among adolescent school children in four Caribbean countries. Methods: Nationally representative cross-sectional data were analysed from 9,143 adolescents (15 years=median age) that took part in the “2016 Dominican Republic, 2016 Suriname, 2017 Jamaica and 2017 Trinidad and Tobago “Global School-Based Student Health Survey (GSHS).” Results: The prevalence of loneliness was 15.3% in four Caribbean countries, ranging from 12.1% in Dominican Republic to 18.6% in Jamaica. In adjusted logistic regression analysis, female sex, having no close friends, older age, anxiety induced sleep disturbance, frequent bullying victimization (≥3 days/month), having been physically attacked, parental emotional neglect, having sustained multiple serious injuries (past year) and not eating fruit and vegetables were associated with loneliness. In addition, in sex stratified adjusted logistic regression analysis, among boys, daily exposure to passive smoking, and being from Suriname, and among girls, frequent experience of hunger, low peer support, trouble from drinking alcohol and high leisure-time sedentary behaviour (≥8 hrs/day) were associated with loneliness. Moreover, in addition to above results, in unadjusted analysis, involvement in physical fight, parents never check on homework, parental disrespect of privacy, frequent school truancy (≥3 days/month), current tobacco use, having no physical education and drinking frequently soft drinks (≥3/day) were associated with loneliness. Conclusion: Almost one in six students reported loneliness and several associated factors were identified which can aid intervention strategies.